Pengaruh Permainan Tradisional Gobak Sodor Terhadap Ketrampilan Motorik - Fakhri, Muh Slamet; Efendi, Abdullah (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
Traditional games are a cultural heritage that plays an important role in supporting child development, especially in terms of motor skills. However, in the digital age, children's interest in traditional games has declined due to the dominance of gadgets and online games, which can potentially hinder the development of gross motor skills such as balance, speed, and agility. Gobak Sodor, as one of Indonesia's traditional games, involves active physical movements such as running, jumping, and maintaining balance, making it a relevant medium for physical education. This study aims to determine the effect of the traditional game of Gobak Sodor on the motor skills of fifth-grade students at MI Matholiul Ulum Menco. The study used a quantitative approach with a one-group pretest–posttest quasi-experimental design. The research subjects consisted of 31 students (12 boys and 19 girls). The instrument used was a motor skills test covering aspects of balance, speed, agility, and coordination. The data were analyzed using normality, homogeneity, and paired sample t-tests to examine the differences between the pretest and posttest results. The results showed a significant improvement in students' motor skills after participating in Gobak Sodor. Posttest scores were consistently higher than pretest scores (p < 0.05) across all indicators. This proves that Gobak Sodor is effective in improving motor skills while fostering cooperation, sportsmanship, and appreciation of local culture. This study contributes to the understanding that traditional games can be integrated into physical education as an innovative and contextual strategy to support children's holistic development.